Geodynamics of heterogeneous gold mineralization in the North China Craton and its relationship to lithospheric destruction - Li, Sheng-Rong; Santosh, M. (Gondwana research, 2017)
The North China Craton (NCC) hosts some of the world-class gold deposits on the globe, which can be classified into distinct types as the “Jiaodong type”, explosive breccia type and skarn type. The “Jiaodong type” gold deposits were formed at ca. 120–130Ma both in the margins and interior of the NCC. Two explosive breccia gold deposits formed at ac. 180Ma and 120Ma and are located in the southern margin and the interior of the NCC. Important skarn gold deposits of ca. 128Ma formed within the interior of the NCC. Although the formation and distribution of these gold deposits are temporally and spatially heterogeneous, they are commonly related with the lithospheric destruction of the NCC. The interplay of several factors such as basement architecture, inhomogeneous decratonization, crust-mantle interaction, mantle dynamics, magmatic characteristics, high heat flow and massive flux of deep-derived ore-forming fluids operated in generating the gold endowment. All the three types of gold systems are closely related with granitoid plutons and different types of dykes, the magmas for which were sourced from the lower crust near the Moho discontinuity and involved the mixing and mingling of felsic and mafic magmas. The ore forming fluids display prominent magmatic signature and were largely derived from deep domains, with probable input from the asthenosphere mantle. The heterogeneous distribution of the giant gold systems in the NCC was geodynamically controlled by the destruction of the craton. The regions at the confluence of two or three Precambrian micro-continental-blocks are generally characterized by thinned lithosphere and high heat flow, constituting the potential sites of giant gold deposits. The mantle beneath these regions shows EM2 characteristics implying the involvement of subducted oceanic components. The magmatic intrusions associated with the gold systems crystallized under high oxygen fugacity conditions and were rich in volatiles. [Display omitted] •Evaluating the heterogeneous basement architecture and gold systems in the North China Craton•Confluence of Precambrian micro-blocks generally bears thinned lithosphere and high heat flow.•The mantle beneath these confluences generally shows EM2 characteristics.•The magma associated with gold system crystallized at high oxygen fugacity and rich volatiles.•Junctions of Precambrian micro-blocks mark potential sites of giant gold deposits.